Proceedings of the Web Conference 2021 2021
DOI: 10.1145/3442381.3449854
|View full text |Cite
|
Sign up to set email alerts
|

Surrounded by the Clouds

Abstract: In the early days of cloud computing, datacenters were sparsely deployed at distant locations far from end-users with high end-toend communication latency. However, today's cloud datacenters have become more geographically spread, the bandwidth of the networks keeps increasing, pushing the end-users latency down. In this paper, we provide a comprehensive cloud reachability study as we perform extensive global client-to-cloud latency measurements towards 189 datacenters from all major cloud providers. We levera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(5 citation statements)
references
References 24 publications
(26 reference statements)
0
5
0
Order By: Relevance
“…The reason could be the lack of business or hosting model, slowness of standardization, or the lack of "killer" applications that would benefit from the lower latency com- VOLUME 4, 2016 pared to the cloud. In fact, it has been demonstrated that the latency from the client devices to the cloud in many parts of the world is already sufficient for most applications [52].…”
Section: Answer To Rq3: What Are the Pros And Cons Of These Methods?mentioning
confidence: 99%
“…The reason could be the lack of business or hosting model, slowness of standardization, or the lack of "killer" applications that would benefit from the lower latency com- VOLUME 4, 2016 pared to the cloud. In fact, it has been demonstrated that the latency from the client devices to the cloud in many parts of the world is already sufficient for most applications [52].…”
Section: Answer To Rq3: What Are the Pros And Cons Of These Methods?mentioning
confidence: 99%
“…The WF-CCRA method is elaborated in Algorithm 2. The first step is to initialize the vectors of parameters and variables used in (1) (or in (2)). Following that, two empty sets, R ′ and Ω, are established.…”
Section: B Wf-ccramentioning
confidence: 99%
“…In these circumstances, a distributed cloud architecture is essential [2], which could be implemented via a solid cloudnetwork integrated infrastructure built of distinct domains in Beyond 5G (B5G) [3]. These domains can be distinguished by the technology employed, including radio access, transport, and core networks, as well as edge, access, aggregation, regional, and central clouds.…”
Section: Introductionmentioning
confidence: 99%
“…The main reason is the fact that computing devices at the disposal of the general public are exactly where they are needed the most -at the edge of the network. In the best possible case, clients would have a direct connection to them, avoiding the so-called last mile, often responsible for the significant fraction of network delay as recent measurement studies show [9,23]. Also, in areas with the dense deployment of cloud datacenters, in-network edge would give mostly minor improvements [10].…”
Section: Background and Motivationmentioning
confidence: 99%